DEVELOPMENT CREATIVITY ON CHILDHOOD ARENA KIDS BALIKPAPAN THROUGH LETTUCE CULTIVATION: HYDRO-DFT SYSTEM FERTIGATION METHOD - Hidayat, Jefri Pandu; Siti Munfarida; Fadli Robiandi; Jaysindri Deo Sattva Dwisar Tonda; Fidela Chosta; Adrian Prananda Putra; Andini Angelina Putri; Theresia Cecilia (Universitas Airlangga, 2024)
Early childhood education (4-6) years is focused on developing creativity in order to create the next generation of problem solvers. The majority of students in the Arena Belajar KIDS learning center tend to overplay on gadgets so that creativity and brain concentration decrease. One solution to break this addiction is to invite students to participate in getting to know nature more closely. This activity aims to increase children's creativity and awareness by cultivating lettuce with the hydro-DFT system. The materials used are lettuce seeds of Lactuca sativa variety, netpot, rockwoll, hydroponic nutrients with a mass ratio (1:5) toward (1:3) on last week. The tools used include water pumps, hoses, TDS & pH meters, and hydro-DFT devices that work with the fertigation system. The final result is the harvest of lettuce after a 30-day planting period with average 19.44 cm plant height, 11.92 number of leaves, and 101.78 gr fresh weight. The harvest was carried out based on the feasibility of lettuce specifications that were fertile above 60%. Lettuce harvest from a total of 20 netpots with the hydro-DFT fertigation system showed 70% cultivation success. The average level of feedback on the program series is very good (4), as evidenced by projects that all goes as schedule and are solutive to partner problems. It is hoped that cooperation with partners will continue so that in the long run it can create independent vegetable gardens in the school or in the home of each student and teacher.